Pengaruh ekstrak biji melinjo terhadap viabilitas dan apoptosis sel hsc-3 (Laporan Penelitian) - Monica Dewi Ranggaini; Johni Halim; Richard Tridarmawan (Fakultas Kedokteran Gigi Universitas Trisakti, 2022)
Background: Squamous cell carcinoma (SCC) is the most common form of oral cancer. SCC treatment generally uses surgical procedures, chemotherapy, etc. Currently there are more than 60% of anticancer compounds obtained from natural ingredients, one of which is Gnetum gnemon L. (G. gnemon L.) or commonly called melinjo. Objective: To determine whether the G. gnemon L. seed ethanolic extract with concentrations of 1, 10, and 100 µg/mL could reduce viability and induce apoptosis in the HSC-3 cell line. Methods: Laboratory experimental research (in vitro) was conducted using the cell line HSC-3. Cells were treated with G. gnemon L. seed ethanolic extract with concentrations of 1, 10, and 100 µg/mL for 24 hours. Ethanol 70% was used as solvent and negative control. Doxorubicin was used as a positive control. The treated cells were analyzed using MTT assay and flow cytometry to examine changes in cell viability and apoptosis that occurred. Results: G. gnemon L. seed ethanolic extract with concentrations of 1, 10, and 100 µg/mL could significantly reduce viability and induce apoptosis in the HSC-3 cell line (p<0.05). The ability to reduce viability increased with the increase in extract concentration as many as 8,169 cells, 5,789 cells, and 3,068 cells and also induces apoptosis by 8.33 ± 0.93%, 16.55 ± 1.51%, and 28.73 ± 0.89% of cells tested sequentially. Conclusion: G. gnemon L. seed ethanolic extract with concentrations of 1, 10, and 100 µg/mL for 24 hours was able to reduce viability and induce apoptosis in the HSC-3 cell line.